Institutional Reforms in the Context of the Future of Europe Conference From the Polish Political Science Perspective - Bajda, Piotr (Maastricht 30: A Central European Perspective, 2025)
The article examines the significance of the expansion of the European Union for post-communist countries in 2004 and afterwards. However, it also shows what added value the expansion to the East represented. The admission of culturally diverse countries with different traditions allowed the construction of Europe in line with the vision adopted in the Treaty of Lisbon. Thanks to Central Europe, it became a fact that the Old Continent was united in diversity, as its slogan says. In this context and from the perspective of the Central European countries, the paper presents an opinion on the latest proposals for changes in the Community treaties. Discussion is critical now when the Russian invasion of Ukraine complicated the geopolitical situation in Central Europe and within the European Union as a whole.Furthermore, the heroic defence of Ukrainians opened the door to the European Union for Kyiv, putting the need to reform EU treaties on the agenda again. However, the proposals for new treaties may paradoxically weaken Europe’s defence, which is even more dangerous for the countries located on the eastern border of the European Union and NATO. Keywords: European Union, Treaty reform, Central Europe, Future of Europe